Computational Fluid Dynamics (CFD) Study of Flow Development in an Eccentric Annulus - Mohamed Nawai, Rahimah (Universiti Teknologi PETRONAS, 2011)
Numerous publications have addressed the problems inherent to calculating wellbore hydraulics in eccentric annulus. CFD modeling provides an alternative approach of investigating fluid flow in such complex geometries. This branch of fluid flow analysis complements experimental and theoretical work, providing economically interesting alternatives through the simulation of real flows and allowing an alternative form for theoretical advances under conditions unavailable experimentally. In this study, results from a series of numerical simulations for the fully developed laminar flow of Newtonian fluids in pipe, concentric and eccentric annular geometries, conducted using the computational fluid dynamics (CFD) code FLUENT, are used to investigate the effect of eccentricity, and friction pressure losses. Unlike the uniform velocity profile applicable for every sector in a concentric annulus, the axial velocity profile for an eccentric annulus is altered, with the peak velocities varying with location. A virtual inspection of the velocity profiles in an eccentric annulus shows that the zone of highest shear exists across the narrowing sector of an eccentric annulus. The project starts with rnuning simulations with pipe to have the basic understanding of how flow in circular geometry will be look like. The simulation results are expected to have flow development with a higher friction factor value at the entrance. As the flow developing, friction factor starts to decrease and become constant showing that it has already in fully developed flow. For concentric annulus, the fluid flow developing to the inner side of the annulus deviating from the walls as towards inside, the resistance is much lesser as compared to near the wall. Next, we did simulations with same properties of fluid flow with eccentric annulus. We found that at very high eccentricities, data from the CFD model yields lower friction pressure. The reason being is due to the velocity is higher to the wider gap as compared to the narrow side. The phenomenon resulted due to the same factor of resistance to flow when the gap between the two geometries is lesser.